Analisis Faktor-Faktor yang Mempengaruhi Perusahaan Mengungkapkan CSR pada Perusahaan High Profile - Maya Aresteria; Deddy Sulestiyono; Rosyadah Fairuz Hitotsu (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2021)
Corporate Social Responsibility (CSR) is a form of corporate responsibility and contribution to the environment and society. Any factors motivate companies to conduct CSR diclosures, namely to obtain recognition of waste treatment, competitive factors, strategies, and financial factors to increase profitability. The company executes CSR disclosures to attract attention of the public and shareholders. But to execute Corporate Social Responsibility (CSR), the firms will spend large costs, and it will be an expense that can reduce firm revenue. Even though by executing CSR, the firms image will get better, and consumer loyalty will be even higher. This sample used in this study are high profile firms listed on the Indonesian Stock Exchange (IDX) during the peride 2017 to 2019. The sample is used by 54 firm and selected by sampling methods. The results of this study show that disclosures CSR influence the profitability firms.